Property booms and bubbles. A demolition strategy - towards a tabula rasa? - -Jansen, Leonie Janssen; Lloyd, Greg (Journal of Surveying, Construction and Property, 2017)
There is a tendency to perversity in the effects of public policy for the built environment at large and with respect to specific sectors. This review paper addresses the unanticipated effects arising from the land and property development incentives which prevailed before the current economic recession. In effect, a perverse outcome resulted in the form of a property bubble. There is now also a perversity in terms of public finances being allocated to correct the dysfunctional market sectors. In particular, the use of a demolition strategy to address the oversupply in the land and property stock is a perverse means of addressing market failure. This paper draws on experiences in the Netherlands, the UK and the Republic of Ireland where economic conditions, political priorities and public expenditure cuts have combined to create a dysfunctional land and property domain. The paper questions whether demolition is the appropriate response to the tensions evident in modern land and property development markets.